Effect of Wind Load on Structural Performance of Dimensionally Regular & Irregular High rise Buildings with different Outrigger Systems - Rohit B. Khade; Prof. Prashant M. Kulkarni (International Journal of Engineering and Management Research, 2019)
Outriggers system is used as one of the best way of increasing the lateral stiffness and has been generally utilized in tall building structures. The outrigger system is very effective in increasing structure’s flexural stiffness. It is likewise viable in decreasing the horizontal top deflection and bending moments in the core of high-rise frame-core structures. This study presents the detailed analysis on how the top drift, inter-story drift, base moment in the core are influenced by the outriggers stiffness, outriggers optimum locations, columns axial stiffness and foundations flexibility. outrigger braced structures can strengthen a structure without disturbing its aesthetic appearance and this is a significant advantage over other lateral load resisting systems. The thesis compare between many outriggers systems including both concrete & steel Outriggers. The Rectangular shape & L- shaped building structures are taken for analysis. The study also presents simplified procedure to optimize the location of the outriggers that will result in a maximum reduction in the lateral displacement at the top of the building. The modeling of the structure is done using “ETABS” program. The investigation of the model is completed by comparable static technique. Finally, the thesis proposed a simplified analysis for outriggers structures with core for both regular and irregular high rise building.